Stable internal fixation with dual plate technique for osteoporotic distal femur fractures. (March 2022) - Lim, Chaemoon; Choi, Sungwook; Choi, Tae Hyun; Kang, Hyunseong
Abstract: Background: Osteoporotic distal femur fractures are difficult in terms of fracture treatment and recovery. We hypothesized that the minimally invasive plate osteosynthesis (MIPO) with dual plate technique increased fixation stability and encouraged early mobilization and return to pre-fracture activity. Material and methods: Between 2016 and 2019, 22 patients were treated with the dual plate technique for osteoporotic distal femur fractures. To evaluate the clinical outcome, the modified Western Ontario and McMaster Universities (WOMAC) score, Tegner activity score, knee range of motion (ROM), time to pain free full weight bearing from operation and patient satisfaction score were used. To evaluate the radiological outcome, the time to radiological union and varus or valgus angulation were measured. Results: The mean modified WOMAC score was 37.0 ± 6.5 (range, 26–42). There was no significant difference between preoperative and postoperative Tegner activity score ( p = 0.436). Among 22 patients, 16 patients (72.7%) achieved preoperative activity level. The mean knee ROM was 106.1° ± 16.8° (range, 80–135). The time to pain free weight bearing was 7.4 ± 1.5 (range, 5–10) weeks. In patient satisfaction, 20 patients (90.9%) were very satisfied or somewhat satisfied. Bone union was achieved in all patients at 16.4 ± 4.3 (range, 13–22) weeks. The final follow-up valgus angle was 3.6° ± 4.0° (range, −2.5° - 10.9). Conclusion: MIPO with the dual plate technique can provide rigid fixation for osteoporotic distal femur fractures. This stable and rigid fixation may allow early mobilization and return to pre-fracture activity. Highlights: Osteoporotic distal femur fractures are difficult in terms of fracture treatment and recovery. The minimally invasive plate osteosynthesis (MIPO) with the dual plate technique can provide rigid fixation for osteoporotic distal femur fractures. This stable and rigid fixation may allow early mobilization and return to pre-fracture activity in elderly patients. The MIPO with the dual plate technique could be useful treatment option for osteoporotic distal femur fractures.